MANAJEMEN ASUHAN KEBIDANAN BERKELANJUTAN POST NATAL PADA NY”W” DENGAN BENDUNGAN ASI HARI KETIGA SAMPAI 31 HARI MASA NIFAS DI PUSKESMAS BARA BARAYA - Raditha Nur Arsy Jamaruddin S; Ferawati Taherong; Syatirah (Jurnal Midwifery, 2022)
Introduction Breast milk dam is the accumulation of milk in the breast due to narrowing of the lactiferous ducts or glands that are not completely emptied during babies’ breastfeeding. It could also occur because of the abnormalities in the nipples of mothers. Breast milk dams usually be found on the third to fifth day after a delivery. The major purpose of this scientific paper was to investigate and implement a sustainable midwifery care management for Mrs "W" with the case of postnatal breastfeeding dam from the third day to the end of the postpartum period at the Bara Baraya Health Center. Method The study was conducted by using the 7-stages of Helen Varney’s midwifery care management approach. Result The findings of this study indicated that there were no obstacles found during the midwifery care on the patient. The diagnosis of a breast milk dam was evaluated by using the subjective data and indicators such as the the feeling of painful and hot. The objective data was also used by looking at the physical problems such as swollen breasts, the hardenign of the nipples, and the increase of the mother’s body temperature. The treatment was provided by administering the anti-pain medication of 500 mg paracetamol to be consumed 3 times a day. Moreover, the mother was also educated on how to do the proper techniques of breastfeeding and breast care. Conclusion This study concluded that this study was done by implementing the 7-stages of Varney management approach and SOAP documentation procedure. During the process of treatment, the condition of the patient was generally good and normal without any complications both on the mother and the baby. The condition of the patient was also evident to become better every day.